Plasma-derived exosomal miRNAs as potentially novel biomarkers for type 2 diabetes mellitus with abdominal obesity - Li, Yan; Wang, Youqin; Li, Zhan; Feng, Lihui; Feng, Ru; Jia, Jia; Xing, Li; Zheng, Lu (Frontiers in Endocrinology, 2025)
AimsTo explore the plasma exosomal miRNA expression profiles in patients with abdominal obesity and type 2 diabetes mellitus (T2DM), identify differentially expressed exosomal m4RNAs, and evaluate the potential of selected exosomal miRNAs as biomarkers for abdominal obesity-related T2DM.MethodsIn the screening phase, high-throughput sequencing was used to detect the plasma exosomal miRNA expression profiles of non-abdominal obese individuals with normal glucose metabolism (NAO/NG, N = 4), abdominal obese individuals with normal glucose metabolism (AO/NG, N = 4), and abdominal obese T2DM patients (AO/T2DM, N = 4). Five differentially expressed miRNAs were identified. In the independent validation phase, RT-qPCR was performed to validate the expression of these miRNAs in the NAO/NG group (N = 18), AO/NG group (N = 14), and AO/T2DM patients (N = 17). The correlation between the miRNA levels in AO/T2DM patients and clinical features was evaluated, and the diagnostic value of the selected miRNAs for AO/T2DM was analyzed using receiver operating characteristic (ROC) curves.ResultsIn the screening phase, 5 exosomal miRNAs showed sequential changes among the NAO/NG, AO/NG, and AO/T2DM groups. The AO/NG group specifically expressed 16 exosomal miRNAs, while the AO/T2DM group specifically expressed 7 exosomal miRNAs. In the independent validation phase, the expression of exosomal miRNAs hsa-let-7g-5p and PC-3p-13356 in plasma increased progressively across the NAO/NG, AO/NG, and AO/T2DM groups. The expression of exosomal hsa-miR-6505-5p in the AO/T2DM group was significantly higher than that in the AO/NG and NAO/NG groups. The expression of hsa-miR-1229-3p in plasma exosomes was significantly lower in the AO/NG group compared to the NAO/NG group, but higher in the AO/T2DM group compared to the AO/NG group. No differences were detected in the expression of hsa-miR-4750-5p among the groups. The areas under the ROC curves (AUC) for plasma exosomal hsa-let-7g-5p, PC-3p-13356, and hsa-miR-6505-5p were 0.857, 0.786, and 0.878, respectively. When combined, these three miRNAs showed high diagnostic value for abdominal obesity T2DM (AUC = 0.891).ConclusionsPatients with abdominal obesity and T2DM have a unique exosomal miRNA expression profiles. These characteristic exosomal miRNAs could serve as novel biomarkers for identifying such patients and may help in further understanding the pathogenesis of abdominal obesity-related T2DM.